Atomic layer deposition-enabled ultrastable freestanding carbon-selenium cathodes with high mass loading for sodium-selenium battery. (January 2018) - Ma, Dingtao; Li, Yongliang; Yang, Jingbo; Mi, Hongwei; Luo, Shan; Deng, Libo; Yan, Chaoyi; Zhang, Peixin; Lin, Zhiqun; Ren, Xiangzhong; Li, Jianqing; Zhang, Han
Abstract: Melt diffusion followed by vapor deposition is judiciously combined with atomic layer deposition (ALD) to construct Al2 O3 –coated (Se/porous N-doped carbon nanofibers)@Se composite (denoted SC@Se-Al2 O3 ) materials for sodium-selenium (Na-Se) batteries. High mass loading, ultrastable and free-standing carbon-selenium cathode is conveniently achieved by tailoring both the Se content and the thickness of deposited Al2 O3 layer. Importantly, in contrast to only 176 mAh g −1 of the electrode without Al2 O3 deposition after 660 cycles, the composite with a Se content of 67 wt% and a 3-nm Al2 O3 thickness retains a reversible capacity of 503 mAh g −1 after 1000 cycles with no capacity fading at 0.5 A g −1 . These findings clearly suggest that ALD strategy provides a viable, controllable and effective means of tuning the electrode performance towards high mass loading of active materials and long cycle life of the resulting battery for energy storage applications. Graphical abstract: Carbon-selenium composites with high Se content and Al2 O3 coating are crafted through a judicious combination of melt diffusion and vapor deposition of Se and atomic layer deposition of Al2 O3 in sequence, exhibiting high discharge capacity and excellent stability for sodium-selenium batteries. Highlights: The ultrastable and freestanding carbon-Se cathodes for Na-Se batteries are prepared. High Se loading with tunable content up to 70 wt% is achieved by two infiltrations. The effect of the Al2 O3 thickness deposited by ALD is systematically studied. The electrode with 67 wt% of Se and 25 Al2 O3 layers exhibits the best performance. This is due to the synergy of N-doped 3D carbon matrix and the Al2 O3 layer protection.